Effect of an acute glucose overload on islet cell morphology and secretory function in the toad - Francini, Flavio (2001)
The aim of this work was to study the effect of induced hyperglycemia on islet cell mass and insulin secretion in normal toads. Immunolabeled β cell area, replication (bromodeoxyuridine) and apoptosis (propidium iodide) rate, islet neogenesis (cytokeratin), and insulin secretion in vitro were measured in adult male specimens of Bufo arenarum during and after interruption of the injection of either a 50% glucose solution (2 g/100 g) or its vehicle for 4 days. Glucose administration caused hyperglycemia (122.6 ± 16.7 and 508.3 ± 115.9 mg/dl vs 23.5 ± 1.26 and 22.8 ± 1.8 mg/dl, at days 3 and 5, respectively, P < 0.05) and a significant decrease in the number of islets/mm2 (day 3: 9.7 ± 0.9 vs 3.3 ± 0.4, P < 0.05; day 5: 9.4 ± 0.8 vs 7.4 ± 0.6; day 9: 9.6 ± 0.9 vs 6.2 ± 0.4, P < 0.05) and in the percentage of immunolabeled β cell area (day 3: 2.07 ± 0.2 vs 0.5 ± 0.1%, P < 0.05; day 5: 1.8 ± 0.1 vs 0.6 ± 0.1%; day 9: 1.7 ± 0.1 vs 0.7 ± 0.1%, P < 0.05). Glucose-injected animals had a simultaneous significantly higher percentage of BrdU-labeled β cells (day 3: 0.46 ± 0.02 vs 0.23 ± 0.03%; day 5: 0.54 ± 0.13 vs 0.22 ± 0.02%; day 9: 0.61 ± 0.0 vs 0.27 ± 0.05%, P < 0.05) and cytokeratin-labeled endocrine cells (day 3: 0.21 ± 0.06 vs 0.01 ± 0.00%; day 5: 0.17 ± 0.06 vs 0.01 ± 0.01%; day 9: 1.25 ± 0.2 vs 0.01 ± 0.008%, P < 0.05) and a higher rate of apoptotic β cells (day 3: 0.14 ± 0.04 vs 0.05 ± 0.02%; day 5: 0.4 ± 0.06 vs 0.05 ± 0.2, P < 0.05; day 9: 0.47 ± 0.04 vs 0.06 ± 0.03, P < 0.05). Comparable amounts of insulin were secreted in vitro by both groups in response to 2 mM glucose, whereas there was a significantly reduced response to 8 mM glucose in treated animals (day 3: 73 ± 12 vs 165 ± 20%; day 5: 74 ± 11 vs 204 ± 18%, P < 0.05). This decreased response to high glucose reverted to normal after removal of the glucose injection. These results show for the first time that short-term hyperglycemia triggers marked morphological and transient secretory changes in the toad pancreas similar in part to those elicited in the pancreas of several mammals. As with other results previously reported, these results support the usefulness of the toad as an alternative easily handled model to study the growth and secretory function of the endocrine pancreas.